Babur Nama : journal of Emperor Babur - Babur, Emperor of Hindustan (New Delhi Rupa Publications, 2017)
A translation of Babur$1 (Bs personal memoir written in Turki, Baburnama remains true to the original, portraying the extraordinary life of the founder of the Mughal Empire in India. Often quoted by historians and academicians alike, this book possesses the rare distinction of being relevant across centuries. Baburnama is the complete record of Babur$1 (Bs life from the time he ascended the throne at the young age of eleven to when he finally established himself as a monarch (1493 to 1529).What fascinates readers even today is Babur$1 (Bs intimate and detailed account of the world around him and what is truly astonishing is that there is no historical precedent for his narrative, making it the first real autobiography in Islamic literature. Annette Susannah Beveridge$1 (Bs nuanced translation offers us a unique insight into this remarkable period in history.s
Keywords: India--Mogul Empire; Babur, Emperor of Hindustan, 1483-1530